Pengaruh Tiga Hari Pemberian Jus Mentimun Terhadap Penurunan Tekanan Darah Penderita Hipertensi: The Effect of of Three Days Cucumber Juice Administration on Lowering Blood Pressure in Hypertension Patients - Erni Yusnita Lalusu; Dwi Wahyu Balebu; Ninik Kurniawati Nurrachmatika; Ramli Ramli; Marselina Sattu; Anang Samudera Otoluwa (Universitas Airlangga, 2025)
Background: Hypertension is one of the leading non-communicable diseases worldwide. In general, non-pharmacological therapy is crucial to minimize side effects and the risk of complications. Cucumber (Cucumis sativus L.) has been proposed as an alternative therapy for hypertension due to the high potassium, magnesium, and water content, along with the diuretic and vasodilatory effects, which can help lower blood pressure. Objectives: This study aims to analyze the effect of 3 days of cucumber juice on lowering blood pressure in hypertension patients. Methods: A pre-experimental study was conducted using a one-group pretest-posttest design. The subjects were 40 randomly selected hypertension patients. The intervention comprised 200 ml of cucumber juice once daily in the afternoon for 3 consecutive days. Blood pressure was measured before and after the intervention and analyzed using Wilcoxon test. Results: The results showed that the mean systolic and diastolic blood pressure before intervention were 166.50 mmHg and 99.25 mmHg, respectively. After the intervention, a significant decrease in mean blood pressure was observed (p-value = 0.001), both systolic (150.38 mmHg) and diastolic (87.85 mmHg). Stratification analysis of covariate subcategories also showed a similar trend. The decrease in blood pressure after cucumber consumption was seen in all subcategories. This indicates that the effect of cucumber in lowering blood pressure is not influenced by various covariates. Conclusions: The mean blood pressure of hypertension patients decreased significantly after cucumber juice consumption, both overall and after, leading to differences in subject characteristics. Further studies need to demonstrate the effectiveness of cucumber juice by adding a control group.